Experimentally derived buoyancy duration of seagrass fragments for biophysical dispersal modelling in the Great Barrier Reef - Douchan Hanuise; Chieh Lin; Samantha Tol; Severine Choukroun; Michael A. Rasheed; Thomas Dobbelaere; Paul H. York; Timothy M. Smith; Robert G. Coles; Emmanuel Hanert; Alana Grech (Marine Environmental Research, 2026)

How atmospheric forcing resolution impacts storm surge model results: Insights from Storm Xaver in the North Sea-Scheldt estuary continuum - Ny Riana Randresihaja; Olivier Gourgue; Lauranne Alaerts; Xavier Fettweis; Jonathan Lambrechts; Miguel De Le Court; Marilaure Grégoire; Emmanuel Hanert (Regional Studies in Marine Science, 2026)

Decadal and multispecies coral connectivity modeling for conservation and restoration prioritization in Florida - Thomas Dobbelaere; Ryan Chabotte; Joana Figueiredo; Daniel M. Holstein; Emmanuel Hanert (Coral Reefs, 2026)

Integrating interspecific traits into biophysical models of seagrass dispersal - Douchan Hanuise; Thomas Dobbelaere; Severine Choukroun; Michael A. Rasheed; Jonathan Lambrechts; Paul H. York; Timothy M. Smith; Robert G. Coles; Emmanuel Hanert; Alana Grech (Ecological Modelling, 2025)

Hydrodynamic impacts of bridge construction and land reclamation on water residence time and flushing processes in Kuwait Bay - Colin Scherpereel; Yousef Alosairi; Jonathan Lambrechts; Emmanuel Hanert (Marine Pollution Bulletin, 2025)

Nubian aquifer linkage to the High Aswan Dam Reservoir: Initial assessments of processes and challenges - Mohamed Ramah; Essam Heggy; Ahmed Nasr; Mostafa Toni; Mohamed M. Gomaa; Emmanuel Hanert; Adel Kotb (Journal of Hydrology, 2024)

Investigating the link between the Port of Miami dredging and the onset of the stony coral tissue loss disease epidemics - Thomas Dobbelaere; Daniel M. Holstein; Lewis J. Gramer; Lucas McEachron; Emmanuel Hanert (Marine Pollution Bulletin, 2024)

Hurricanes enhance coral connectivity but also superspread coral diseases - Thomas Dobbelaere; Apolline Dekens; Antoine Saint‐Amand; Lauranne Alaerts; Daniel M. Holstein; Emmanuel Hanert (Global Change Biology, 2024)
Climate change poses an existential threat to coral reefs. A warmer and more acidic ocean weakens coral ecosystems and increases the intensity of hurricanes. The wind–wave–current interactions during a hurricane deeply change the ocean circulation patterns and hence potentially affect the dispersal of coral larvae and coral disease agents. Here, we modeled the impact of major hurricane Irma (September 2017) on coral larval and stony coral tissue loss disease (SCTLD) connectivity in Florida's Coral Reef. We coupled high‐resolution coastal ocean circulation and wave models to simulate the dispersal of virtual coral larvae and disease agents between thousands of reefs. While being a brief event, our results suggest the passage of hurricane Irma strongly increased the probability of long‐distance exchanges while reducing larval supply. It created new connections that could promote coral resilience but also probably accelerated the spread of SCTLD by about a month. As they become more intense, hurricanes' double‐edged effect will become increasingly pronounced, contributing to increased variability in transport patterns and an accelerated rate of change within coral reef ecosystems.

Assessing coral reef conservation planning in Wakatobi National Park (Indonesia) from larval connectivity networks - Irfana Diah Faryuni; Antoine Saint-Amand; Thomas Dobbelaere; Widyastuti Umar; Jamaluddin Jompa; Abigail Mary Moore; Emmanuel Hanert (Coral Reefs, 2024)

How fine is fine enough? Effect of mesh resolution on hydrodynamic simulations in coral reef environments - Antoine Saint-Amand; Jonathan Lambrechts; Christopher J. Thomas; Emmanuel Hanert (Ocean Modelling, 2023)

Seychelles Plateau's oil spill vulnerability - Alex Verhofstede; Thomas Dobbelaere; Jérôme Harlay; Emmanuel Hanert (Marine Pollution Bulletin, 2023)

A multiscale ocean modelling system for the central Arabian/Persian Gulf: From regional to structure scale circulation patterns - Emmanuel Hanert; Aboobacker Valliyil Mohammed; Subramanian Veerasingam; Thomas Dobbelaere; Valentin Vallaeys; Ponnumony Vethamony (Estuarine, Coastal and Shelf Science, 2023)

Larval dispersal patterns and connectivity of Acropora on Florida’s Coral Reef and its implications for restoration - Samantha King; Antoine Saint-Amand; Brian K. Walker; Emmanuel Hanert; Joana Figueiredo (Frontiers in Marine Science, 2023)
Since the 1980s, populations of Acropora cervicornis and A. palmata have experienced severe declines due to disease and anthropogenic stressors; resulting in their listing as threatened, and their need for restoration. In this study, larval survival and competency data were collected and used to calibrate a very high-resolution hydrodynamic model (up to 100m) to determine the dispersal patterns of Acropora species along the Florida’s Coral Reef. The resulting connectivity matrices was incorporated into a metapopulation model to compare strategies for restoring Acropora populations. This study found that Florida’s Coral Reef was historically a well-connected system, and that spatially selective restoration may be able to stimulate natural recovery. Acropora larvae are predominantly transported northward along the Florida’s Coral Reef, however southward transport also occurs, driven by tides and baroclinic eddies. Local retention and self-recruitment processes were strong for a broadcast spawner with a long pelagic larval duration. Model simulations demonstrate that it is beneficial to spread restoration effort across more reefs, rather than focusing on a few reefs. Differences in population patchiness between the Acropora cervicornis and A. palmata drive the need for different approaches to their management plans. This model can be used as a tool to address the species-specific management to restore genotypically diverse Acropora populations on the Florida’s Coral Reef, and its methods could be expanded to other vulnerable populations.

Climate Change Will Fragment Florida Stone Crab Communities - Lauranne Alaerts; Thomas Dobbelaere; Philip M. Gravinese; Emmanuel Hanert (Frontiers in Marine Science, 2022)
Many marine species have been shown to be threatened by both ocean acidification and ocean warming which are reducing survival, altering behavior, and posing limits on physiology, especially during earlier life stages. The commercially important Florida stone crab, Menippe mercenaria , is one species that is affected by reduced seawater pH and elevated seawater temperatures. In this study, we determined the impacts of reduced pH and elevated temperature on the distribution of the stone crab larvae along the West Florida Shelf. To understand the dispersion of the larvae, we coupled the multi-scale ocean model SLIM with a larval dispersal model. We then conducted a connectivity study and evaluated the impacts of climate stressors by looking at four different scenarios which included models that represented the dispersion of stone crab larvae under: 1) present day conditions as modelled by SLIM for the temperature and NEMO-PISCES for the pH, 2) SSP1-2.6 scenario (-0.037 reduction in pH and +0.5°C compared to present-day conditions), 3) SSP2-4.5 scenario(-0.15 reduction in pH and +1.5°C) and 4) SSP5-8.5 scenario (-0.375 reduction in pH and +3.5°C). Our results show a clear impact of these climate change stressors on larval dispersal and on the subsequent stone crab distribution. Our results indicate that future climate change could result in stone crabs moving north or into deeper waters. We also observed an increase in the number of larvae settling in deeper waters (defined as the non-fishing zone in this study with depths exceeding 30 m) that are not typically part of the commercial fishing zone. The distance travelled by larvae, however, is likely to decrease, resulting in an increase of self-recruitment and decrease of the size of the sub-populations. A shift of the spawning period, to earlier in the spring, is also likely to occur. Our results suggest that habitats in the non-fishing zone cannot serve as a significant source of larvae for the habitats in the fishing zone (defined as water depth< 30 m) since there is very little exchange (< 5% of all exchanges) between the two zones. These results indicate that the stone crab populations in Florida may be susceptible to community fragmentation and that the management of the fishery should consider the potential impacts of future climate change scenarios.

Connecting the Dots: Transmission of Stony Coral Tissue Loss Disease From the Marquesas to the Dry Tortugas - Thomas Dobbelaere; Daniel M. Holstein; Erinn M. Muller; Lewis J. Gramer; Lucas McEachron; Sara D. Williams; Emmanuel Hanert (Frontiers in Marine Science, 2022)
For the last 7 years, Florida’s Coral Reef (FCR) has suffered from widespread and severe coral loss caused by stony coral tissue loss disease (SCTLD). First observed off the coast of Miami-Dade county in 2014, the outbreak has since spread throughout the entirety of FCR and some areas of the Caribbean. However, the propagation of the disease through FCR seemed to slow down when it reached the western end of the Marquesas in August 2020. Despite being present about 30 km (∼20 miles) from the Dry Tortugas (DRTO), SCTLD was not reported in this area before May 2021. As SCTLD transmission is likely to be waterborne, here we suggest that this apparently delayed propagation is related to eddy activity near the DRTO under the influence of the Loop Current/Florida Current system. To quantify the impact of the local ocean circulation on the spread of SCTLD from the Marquesas and the DRTO, we evaluated the hydrodynamic-predicted connectivity between these two regions using a high-resolution hydro-epidemiological model between May 2018 and May 2021. Our results suggest that the Marquesas and the DRTO were not connected during February-October 2020 and January-May 2021. These periods coincided with either the occurrence of Tortugas gyres and mean circulation with an eastward component between the Marquesas and the DRTO or the presence of southward currents. Our results suggest that disease agents probably reached the DRTO in November 2020 and that they most likely originated from southern or northwestern reefs of the Marquesas. This study provides novel insight into the role played by the hydrodynamics in the spread of SCTLD within the western-most edge of FCR, and in propagating the disease to uninfected locations.

Coupled Epidemio-Hydrodynamic Modeling to Understand the Spread of a Deadly Coral Disease in Florida - Thomas Dobbelaere; Erinn M. Muller; Lewis J. Gramer; Daniel M. Holstein; Emmanuel Hanert (Frontiers in Marine Science, 2020)
For the last six years, the Florida Reef Tract (FRT) has been experiencing an outbreak of the Stony Coral Tissue Loss Disease (SCTLD). First reported off the coast of Miami-Dade County in 2014, the SCTLD has since spread throughout the entire FRT with the exception of the Dry Tortugas. However, the causative agent for this outbreak is currently unknown. Here we show how a high-resolution bio-physical model coupled with a modified patch Susceptible-Infectious-Removed epidemic model can characterize the potential causative agent(s) of the disease and its vector. In the present study, the agent is assumed to be transported within composite material (e.g., coral mucus, dying tissues, and/or resuspended sediments) driven by currents and potentially persisting in the water column for extended periods of time. In this framework, our simulations suggest that the SCTLD is likely to be propagated within neutrally buoyant material driven by mean barotropic currents. Calibration of our model parameters with field data shows that corals are diseased within a mean transmission time of 6.45 days, with a basic reproduction number slightly above 1. Furthermore, the propagation speed of the disease through the FRT is shown to occur for a well-defined range of values of a disease threshold, defined as the fraction of diseased corals that causes an exponential growth of the disease in the reef site. Our results present a new connectivity-based approach to understand the spread of the SCTLD through the FRT. Such a method can provide a valuable complement to field observations and lab experiments to support the management of the epidemic as well as the identification of its causative agent.

Fine-Scale Coral Connectivity Pathways in the Florida Reef Tract: Implications for Conservation and Restoration - Charles Frys; Antoine Saint-Amand; Matthieu Le Hénaff; Joana Figueiredo; Alyson Kuba; Brian Walker; Jonathan Lambrechts; Valentin Vallaeys; David Vincent; Emmanuel Hanert (Frontiers in Marine Science, 2020)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Predicting the cumulative effect of multiple disturbances on seagrass connectivity - Alana Grech; Emmanuel Hanert; Len McKenzie; Michael Rasheed; Christopher Thomas; Samantha Tol; Mingzhu Wang; Michelle Waycott; Jolan Wolter; Rob Coles (Global Change Biology, 2018)
The rate of exchange, or connectivity, among populations effects their ability to recover after disturbance events. However, there is limited information on the extent to which populations are connected or how multiple disturbances affect connectivity, especially in coastal and marine ecosystems. We used network analysis and the outputs of a biophysical model to measure potential functional connectivity and predict the impact of multiple disturbances on seagrasses in the central Great Barrier Reef World Heritage Area (GBRWHA), Australia. The seagrass networks were densely connected, indicating that seagrasses are resilient to the random loss of meadows. Our analysis identified discrete meadows that are important sources of seagrass propagules and that serve as stepping stones connecting various different parts of the network. Several of these meadows were close to urban areas or ports and likely to be at risk from coastal development. Deep water meadows were highly connected to coastal meadows and may function as a refuge, but only for non‐foundation species. We evaluated changes to the structure and functioning of the seagrass networks when one or more discrete meadows were removed due to multiple disturbance events. The scale of disturbance required to disconnect the seagrass networks into two or more components was on average >245 km, about half the length of the metapopulation. The densely connected seagrass meadows of the central GBRWHA are not limited by the supply of propagules; therefore, management should focus on improving environmental conditions that support natural seagrass recruitment and recovery processes. Our study provides a new framework for assessing the impact of global change on the connectivity and persistence of coastal and marine ecosystems. Without this knowledge, management actions, including coastal restoration, may prove unnecessary and be unsuccessful.

Unstructured-mesh modeling of the Congo river-to-sea continuum - Yoann Le Bars; Valentin Vallaeys; Éric Deleersnijder; Emmanuel Hanert; Loren Carrere; Claire Channelière (Ocean Dynamics, 2016)

How to avoid unbounded drug accumulation with fractional pharmacokinetics - Maud Hennion; Emmanuel Hanert (Journal of Pharmacokinetics and Pharmacodynamics, 2013)

A comparison of three Eulerian numerical methods for fractional-order transport models - Emmanuel Hanert (Environmental Fluid Mechanics, 2010)

On the mathematical stability of stratified flow models with local turbulence closure schemes - Eric Deleersnijder; Emmanuel Hanert; Hans Burchard; Henk A. Dijkstra (Ocean Dynamics, 2008)